Drug utilization in patients with SARS-CoV-2 in an intensive care unit - Miguel Sevilla Méndez; Ana M. Téllez López; Giovanni Gómez Barragán; Ivette Reyes Hernández; Claudia Velázquez González; Isis B. Bermúdez Camps (GarVal Editorial Ltda., 2022)
Context: Prescription indication studies allow identifying the problems that arise during the use of the drug. Aims: To evaluate the treatments used in patients diagnosed with SARS-CoV-2 infection hospitalized in critical care service, through a prescription indication study. Methods: A longitudinal observational study of medication use of the indication-prescription type with elements of the therapeutic scheme and practical consequences was carried out. The sample was characterized from the sociodemographic, clinical, and pharmacotherapeutic points of view. The prescription was evaluated through the indicators: indication, therapeutic scheme, treatment individualization, and drug combinations. The detected adverse reactions were classified according to their causality by the Naranjo Algorithm, their severity, their clinical significance, and according to their mechanism by Rawlins and Thompson. Results: In the sample (n = 77), the male gender predominated (79%) between 27-59 years old (64%), alcohol consumer (62%), hypertensive (33%) with long hospital stay (51%). A total of 417 medications were analyzed, being antibiotics (50.6%) the most prescribed. 73.4% of the therapeutic schemes were correct; however, 26.6% had problems with the therapeutic schemes due to incorrect doses, intervals, duration of treatment, and risky interactions. According to Rawlins and Thompson, two probable adverse reactions were detected, mild, non-serious, and type A and B. Conclusions: The results obtained will allow the pharmaceutical professional to create risk matrices that guarantee a timely intervention in the health team to contribute to the rational and safe use of medicines in patients infected with SARS-CoV-2.